KEBOLEHKESANAN HALAL DALAM INDUSTRI LOGISTIK DI MALAYSIA: TINJAUAN LITERATUR SISTEMATIK: Halal Traceability in the Logistics Industry in Malaysia: A Systematic Literature Review - Shahruddin, Mohamad I’rfan; Kamri, Nor’azzah; Sarif, Suhaili (Online Journal of Islamic Management and Finance (OJIMF), 2025)
The global acceptance of halal logistics has increased due to the demand for quality control and safety measures. While Malaysia is a leader in the halal industry, there remains a need for improved halal traceability systems to guarantee product integrity throughout the supply chain. This paper explores the elements of halal traceability that enhance halal integrity in halal logistics. A systematic review of articles published between 2013 and 2024 focused on traceability, integrity, and halal logistics, particularly third-party logistics (3PL). From an initial pool of 318 articles, 27 were identified as highly relevant. The study identifies five elements vital to developing an efficient traceability system, which are halal certification (HC), documentation and halal policy (DHP), technology management (TM), and human resources management (HR). Those elements are important to make the traceability system relevant to sustaining the halal industry. The findings show that integrating traceability systems in halal logistics is vital in maintaining halal product integrity throughout the supply chain. The synergy between halal certification, policy, technology such as TMS, WMS, blockchain, and a trained workforce is required to maintain halal status. This holistic approach not only improves halal traceability and consumer trust but also supports the sustainability of the halal industry in line with the Sustainable Development Goals.